2019
DOI: 10.1093/ibd/izz183
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Cost for Children Newly Diagnosed With Inflammatory Bowel Disease

Abstract: Background The increasing incidence of pediatric inflammatory bowel disease (IBD), along with more extensive and severe disease in children, raises concern for related health care expenditures. Aim The aim of this study was to quantify and characterize costs of pediatric IBD in the year following diagnosis. Methods We identified all patients diagnosed with IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In addition, utilisation of anti‐TNF medications was the main costs driver, accounting for 64% and 31% of the total cost of CD and UC, respectively 16 . Fondell et al 17 examined direct costs in a small cohort of children recently diagnosed with IBD in the year following the diagnosis. Despite early disease course, infusion costs comprised 37% of all direct costs, indicating an early introduction of biologics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, utilisation of anti‐TNF medications was the main costs driver, accounting for 64% and 31% of the total cost of CD and UC, respectively 16 . Fondell et al 17 examined direct costs in a small cohort of children recently diagnosed with IBD in the year following the diagnosis. Despite early disease course, infusion costs comprised 37% of all direct costs, indicating an early introduction of biologics.…”
Section: Discussionmentioning
confidence: 99%
“…An aim of its application was to decrease the financial burden of IBD care; adults with IBD have annual out of pocket costs greater than two times those of adults without IBD, and costs due to missed work outweigh out of pocket costs [ 16 ]. Concerningly, medical costs associated with pediatric IBD are predicted to be higher than those with adult-onset disease [ 17 , 18 , 19 ], and data are limited regarding financial and time costs for their parents due to missed work.…”
Section: Discussionmentioning
confidence: 99%
“…Fondell et al found that infusion therapy is a driving cost for newly diagnosed cases, followed by hospitalization and outpatient procedures, oral medications, imaging, and visits. 11 In addition to high medical management costs, patients also endure the psychological impacts of the disease on quality of life. Depression and anxiety associated with the condition can perpetuate lower adherence to medical regimens and increased cost of care.…”
Section: ■ Costsmentioning
confidence: 99%
“…In the subgroup who underwent a CD-related surgery, cost per patient/year reached $101,013, likely in part due to procedures such as intestinal resection, colostomies, endoscopic balloon dilation, and stricturoplasty. Fondell et al found that infusion therapy is a driving cost for newly diagnosed cases, followed by hospitalization and outpatient procedures, oral medications, imaging, and visits 11. In addition to high medical management costs, patients also endure the psychological impacts of the disease on quality of life.…”
Section: Costsmentioning
confidence: 99%